Driftwood Bay - Hannon, Irene (Hannon, Irene. Hope Harbor, 2019)
After tragedy upends her world, Jeanette Mason retreats to the tiny Oregon seaside town of Hope Harbor to create a new life. Vowing to avoid emotional attachments, she focuses on running her lavender farm and tearoom - until a new neighbor with a destructive dog and a forlorn little girl invades her turf. But she needn't worry. Dr. Logan West is too busy coping with an unexpected family, a radical lifestyle change, and an unruly pup to have any interest in his reclusive neighbor. Yet when Jeanette and Logan find themselves pulled into the life of a tattered family fleeing persecution in war-torn Syria, might they discover that love sometimes come calling when it's least expected.